ANALISIS FAKTOR YANG BERHUBUNGAN DENGAN KUNJUNGAN MASYARAKAT USIA PRODUKTIF (15-64 TAHUN) DI POSBINDU PTM PURI PRAJA WILAYAH KERJA PUSKESMAS MULYOHARJO,PEMALANG - Arininda Rima Kurnia; Laksmono Widagdo; Bagoes Widjanarko (Jurnal Kesehatan Masyarakat (Undip), 2017)
Non Communicable Disease (NCD) cases are increasing in the productive age caused by unhealthy lifestyle of society. Posbindu PTM aims to be preventive attempt and early detection of NCD so the healthiness in the productive age can be maintained and monitored as well. Posbindu PTM PuriPraja that the reach of it’s activities far from set target (10%) less than 5% in 2016.Number of visits of the productive age population decreased from 2015 to 2016. So, this research aims to analyze factors that correlate with the visit of productive age society in Posbindu PTM PuriPraja, Community Health Center of Mulyoharjo working area, Pemalang. This research use quantitative approach with cross sectional design. Sample of this research are total population of productive age society who visit Posbindu PTM PuriPraja in 2017. Data collection was conducted through interview with questionnaire. Analysis that is used are univariate and bivariate. Chi-Square test result showed that sex (p=0,049), marital status (p=0,029), knowledge (p=0,000), attitude (p=0,000), cadre support (p=0,004) are correlated with the visit of productive age society in Posbindu PTM PuriPraja. While, age (p=0,444), education (p=0,429), job (p=0,139), convenience access (p=0,247), family support (p=0,193), and neighbor support (p=0,350) are not correlated with the visit of productive age society in Posbindu PTM PuriPraja.Correlated sex, marital status, knowledge, attitude and cadre support with the visit of productive age society in Posbindu PTM PuriPraja. Efforts to increase socialization activities and the optimal role of cadres and community leaders.